MULTIKULTURALISME INDONESIA (STUDI PERBANDINGAN ANTARA KONSEP MADANI NURCHOLISH MADJID DAN KONSEP CIVIL SOCIETY) - Agustinus Wisnu Dewantara (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Multiculturalism is difficult to define. As a descriptive term, it has been taken to refer to cultural diversity. As a normative term, multiculturalism implies a positive endorsement, even celebration, of communal diversity, typically based on either the right of different groups to respect and recognize, or to the alleged benefits to the larger society of moral and cultural diversity”. What about Indonesia? In fact, Indonesian cultures indicate the multiculturalism. Is that similar with the concept of “madani”? What about with the concept of the civil society? Which one can adapt in Indonesia? In the cultural environment of Indonesia, cultures are not only interacted or isolated. Those two strategies work at the same time and apply to different aspects of cultures to create new forms of cultures. Multiculturalism can be defined in a ways that go beyond human activities to give a vivid multi-dimensional understanding of cultural interaction, cultural isolation and phenomena between these two extremes